Between sins : redemption is letting go [videorecording (DVD)] - Miller, Carlos; Taylor, George; Duval, Rigoberto; Johnson, Carolyn (Actress) (Buffalo 8, 2023)
After serving five years in prison, Coy returns home with the determination to avoid the people and situations that sent him down a path astray from his religious roots. Almost immediately, Coy is thrown into having to care for his ill mother and adapt to being a father to an estranged daughter. Once Pudda, Coy's old friend, comes back around expecting their street life to resume, Coy's determination to change is put to the test.